(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті з’ясовано поняття «кроскультура», визначено сутність кроскультурного аспекту в освіті, а також причини його появи в освітньому процесі. Ключові слова: освіта, кроскультура, полікультура, мультикультуралізм. The article examines a concept «crossculture», defines the essence of a crosscultural aspect in education and also the reasons of its appearance in educational process. Key words: education, crossculture, polyculture, multiculturalism.